Living with psychosis in West and Southeast Africa: SUCCEED Africa’s four-country situation analysis - Olubukola Omobowale; Rachel Greenley; Grace Ryan; Olusegun Ogunmola; Lloyd Dzapasi; Abraham Jimmy; Anthony Sefasi; Mayowa Olusanmi; Rebecca Esliker; Alhaji Koroma; Adeola Afolayan; Rita Tamambang; et al. (Cambridge Prisms: Global Mental Health)
As part of the formative work of the SUCCEED Africa consortium, we followed a participatory process to identify existing gaps and resources needed for the development and implementation of a rights-based intervention for people with lived experience of psychosis in Malawi, Nigeria, Sierra Leone and Zimbabwe.